Hemi-Slant Lightlike Submanifolds of Indefinite Kenmotsu Manifolds. (13th September 2012) - Haider, S. M. Khursheed; Thakur, Mamta; Advin,
Abstract : We introduce and study hemi-slant lightlike submanifolds of an indefinite Kenmotsu manifold. We give an example of hemi-slant lightlike submanifold and establish two characterization theorems for the existence of such submanifolds. We prove some theorems which ensure the existence of minimal hemi-slant lightlike submanifolds and obtain a condition under which the induced connection ∇ on M is a metric connection. An example of proper minimal hemi-slant lightlike submanifolds is also given.